2016
DOI: 10.1177/0958928716645074
|View full text |Cite
|
Sign up to set email alerts
|

Distributional impacts of cash allowances for children: A microsimulation analysis for Russia and Europe

Abstract: This paper analyses programmes of cash allowances for children and compares their effectiveness in combating child poverty in Russia and four EU countries representing alternative family policy models -Sweden, Germany, Belgium and the United Kingdom.Using microsimulation models, this paper estimates the potential gains if the Russian system were re-designed along the policy parameters of these countries and vice versa. The results confirm that the poverty impact of the program design is smaller than that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…According to the research (Szarfenberg, 2018) the support contributes to the decrease in poverty in Poland, especially in large families (Brzeziński, Najsztub, 2018). A similar scheme can be observed in other countries (Popova, 2016). It can be found in the literature that money transfers are significant for the families for health, educational and employability reasons as well as higher salaries when the children grow up (Aizer et al 2016;Carneiro et al 2015).…”
Section: Family 500+ Programme Versus Polish Pro-family Policysupporting
confidence: 69%
“…According to the research (Szarfenberg, 2018) the support contributes to the decrease in poverty in Poland, especially in large families (Brzeziński, Najsztub, 2018). A similar scheme can be observed in other countries (Popova, 2016). It can be found in the literature that money transfers are significant for the families for health, educational and employability reasons as well as higher salaries when the children grow up (Aizer et al 2016;Carneiro et al 2015).…”
Section: Family 500+ Programme Versus Polish Pro-family Policysupporting
confidence: 69%
“…Research has found that a combination of universal and targeted (means-tested) cash benefits is most effective in reducing child poverty, with an important prerequisite – a sufficient budget (Levy et al, 2007; Popova, 2016). However, countries’ overall tax-benefit systems and population characteristics should not be neglected (Avram and Militaru, 2016).…”
Section: Public Support For Children: Goals and Policies In Practicementioning
confidence: 99%
“…The previous studies of the redistribution in Russia focused on the impact assessment of separate policy instruments, such as child and maternity benefits (Denisova et al, 2000;Ovcharova and Popova, 2005;Ovcharova et al, 2007;Notten and Gassmann, 2008;Popova, 2016;Popova, 2013), in-kind benefits and subsidies (Volchkova et al, 2006), direct taxes (Duncan, 2014) or indirect taxes (Decoster, 2003).…”
Section: Current Macroeconomic Environment With Continuous Recession mentioning
confidence: 99%